2018
DOI: 10.3390/md16100386
|View full text |Cite
|
Sign up to set email alerts
|

Kororamides, Convolutamines, and Indole Derivatives as Possible Tau and Dual-Specificity Kinase Inhibitors for Alzheimer’s Disease: A Computational Study

Abstract: Alzheimer’s disease (AD) is becoming one of the most disturbing health and socioeconomic problems nowadays, as it is a neurodegenerative pathology with no treatment, which is expected to grow further due to population ageing. Actual treatments for AD produce only a modest amelioration of symptoms, although there is a constant ongoing research of new therapeutic strategies oriented to improve the amelioration of the symptoms, and even to completely cure the disease. A principal feature of AD is the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 103 publications
(177 reference statements)
1
15
0
1
Order By: Relevance
“…These HBs are established with residues F67, V70, K85, D133, V135, R141, Q185, C199 and D200. Most of the listed aminoacidic residues are configuring the ATP binding pocket ( Figure 4B) [16,29,30,72]. For the substrate binding pocket, we found sixteen important HBs.…”
Section: Binding Of Meridianins and Lignarenone B To The Atp And Subsmentioning
confidence: 88%
See 2 more Smart Citations
“…These HBs are established with residues F67, V70, K85, D133, V135, R141, Q185, C199 and D200. Most of the listed aminoacidic residues are configuring the ATP binding pocket ( Figure 4B) [16,29,30,72]. For the substrate binding pocket, we found sixteen important HBs.…”
Section: Binding Of Meridianins and Lignarenone B To The Atp And Subsmentioning
confidence: 88%
“…The modelled protein structures and the marine molecules were employed as input of the calculations executed over each of the two cavities using Itzamna software tool [51]. More details on this approach can be found in the literature [29,30].…”
Section: Docking Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kororamides A and B (11a-11b, Figure 11) are tribrominated indolic derivatives isolated from the bryozoan Amathia tortuosa [170,171]. A computational study on kororamides as well as on convolutamines (7, Figure 8) suggested they could act as tau and dual-specificity kinase inhibitors for Alzheimer's disease [172].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Convolutamine F also displayed inhibitory effect for cell division of fertilized sea urchin eggs [46]. Convolutamines I-J, isolated from the Southern Ocean bryozoan A. tortuosa Tenison-Woods, 1880, were recently validated as potential ATP competitive inhibitors [47]. Lutamides A and C exhibited inhibition against adriamycin (ADM)-resistant P388/ADM, vincristine (VCR)-resistant P388/VCR and KB/VJ300 cells in the presence of ADM or VCR whose concentration did not affect growth of the cells examined [44].…”
Section: Convolutamides Convolutamydines and Convolutaminesmentioning
confidence: 99%